Policy of Uptd Information and Communication Technology Education And Culture (TIKPK) Banten Province in Improving the Quality of Human Resources: a Study in Pandeglang Regency - Ariyan, Said; Anwar, Saepul (Ethics and Law Journal: Business and Notary, 2023)
This study aims to analyze the policy of the Regional Technical Implementation Unit for Educational and Cultural Information and Communication Technology (UPTD TIKPK) of Banten Province in improving human resource quality in Pandeglang Regency. The research uses a qualitative descriptive approach to provide a comprehensive overview of policy implementation and its influencing factors. Data were collected through interviews with key informants, field observations, and documentation studies. The analysis was conducted based on Van Meter and Van Horn’s (1975) policy implementation theory, which highlights six main factors: policy standards and objectives, resources, implementing agency characteristics, disposition of implementers, inter-organizational communication, and social, economic, and political conditions. The results show that the UPTD TIKPK policy has been fairly effective in enhancing human resource capacity, particularly through training programs and digital literacy development. However, several challenges remain, including limited infrastructure, insufficient budget support, and suboptimal inter-agency coordination. In conclusion, the success of human resource development through TIKPK policy depends largely on policy actor synergy, resource adequacy, and program sustainability in responding to technological advancement.